(untitled) (Research, Society and Development, 2021)
Alzheimer’s disease (AD) is understood today as a series of stages, beginning with an abnormal process of protein accumulation in the brain, through the well-known Alzheimer’s-like Minor Neuro Cognitive Disorder to the noticeable stages of the disease. AD is considered to be a serious health problem worldwide, with a high increase in incidence. Despite this, there is no effective treatment for its cure. However, non-pharmacological treatments have shown good results to mitigate the cognitive and motor losses presented by their patients, most recently has gained prominence in studies, the photobiomodulation therapy. Thus, the aim of this study is to carry out an integrative literature review of the therapeutic impact of photobiomodulation in the treatment of Alzheimer’s Disease. From the PICOS strategy, the search strategy was performed using the descriptors: Photobiomodulation, Alzheimer’s Disease, Transcranial Photobiomodulation, Cognition, in english, portuguese and spanish, in the PubMed, MEDLINE, LILACS and Scielo databases, between January 2011 and January 2021, following the inclusion and exclusion criteria of the articles. In total, 7 articles met all the criteria and objective of the present study. The research involving photobiomodulation in patients with Alzheimer’s disease is still scarce and relatively recent, however, the results already obtained are significant and promising, since they present indications that it is possible to reverse some pictures of cognitive losses through cellular changes and circulatory improvements, measured through cognitive tests and imaging exams, respectively. The present study can conclude that photobiomodulation, although it still presents some divergences as to its applicability, has a positive impact on the treatment of Alzheimer’s disease, for through the numerous alterations it promotes in the brain, it enables the improvement of cognitive functions, daily functional abilities, and quality of life. Thus, more studies are necessary to elucidate the gaps still existing about photobiomodulation in humans with Alzheimer’s disease.